Stages of Investigation Crimes as a Principle of Construction of Criminal Methods - BEKBULATOV, Aslan (Journal of Advanced Research in Law and Economics, 2018)
Analyzing the different points of view, the author comes to the conclusion that, the process of investigation is not only a prerequisite for its technological development, but also a natural consequence aimed at revealing and investigating the crime and is implemented not in a single process, but in stages. Given the complexity of investigative activities in the detection and investigation of crimes, the technological development of certain forensic processes is expedient and requires its distribution to relatively independent parts (stages).